CELLULAR REACTIONS TO WAX-LIKE MATERIALS FROM ACID-FAST BACTERIA : THE UNSAPONIFIABLE FRACTION FROM THE TUBERCLE BACILLUS, STRAIN H-37 - Sabin, F. R. (The Rockefeller University Press, 1935)
1. The unsaponifiable fractions of the Mycobacteria, though insoluble in water and extremely stable chemical compounds, are nevertheless remarkable stimulants of cells. 2. They give rise to new monocytes which surround these waxes and then fuse into giant cells which engulf them. 3. The property of acid-fastness of the waxes makes it possible to identify them within the giant cells which have phagocytized them. 4. Within the foreign body giant cells the waxes are slowly disintegrated. They appear not to damage the cells which engulf them, and hence one may infer that they take no part in caseation. 5. They have no effect on the resistance of the host.